Financial Leverage and Firms’ Performance: Empirical Investigation of KSE-100 Index - Farhan Ahmed; Iqra Awais; Muhammad Kashif (ETIKONOMI, 2018)
Capital generation to fund everyday operations and long-term expansions is a constant concerning element in the corporate world. This study aims to investigate the optimal level of capital structure that firms can adopt to improve their financial performance given the industry dynamics and economic circumstances of the country. Using Hausman’s specification test, annual data for the period 2005 – 2014 of Karachi Stock Exchange (KSE) 100 index listed securities has been collected to analyze the impact of financial leverage on the firms’ performance. Return on assets, return on Equity, and TOBIN’s Q are the proxies of financial performance analyzed against financial leverage for the KSE 100 index listed firms. The finding of the paper indicates that capital structure, leverage, interest cover and sales growth as most significant variables impacting firms’ profitability.   DOI: 10.15408/etk.v17i1.6102